2007
DOI: 10.4049/jimmunol.179.5.3126
|View full text |Cite
|
Sign up to set email alerts
|

gp340 Expressed on Human Genital Epithelia Binds HIV-1 Envelope Protein and Facilitates Viral Transmission

Abstract: During sexual transmission of HIV in women, the first cells likely to be infected are submucosal CD4+ T cells and dendritic cells of the lower genital tract. HIV is segregated from these target cells by an epithelial cell layer that can be bypassed even when healthy and intact. To understand how HIV penetrates this barrier, we identified a host protein, gp340, that is expressed on genital epithelium and binds the HIV envelope via a specific protein-protein interaction. This binding allows otherwise subinfectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 50 publications
1
47
0
Order By: Relevance
“…It is still debatable whether or not these cell types support active HIV-1 infection (Asin et al, 2004). Although epithelial cells of the FRT may or may not support active HIV-1 infection, they have been shown to transmit infectious virus to target cells (Stoddard et al, 2007). …”
Section: Resultsmentioning
confidence: 99%
“…It is still debatable whether or not these cell types support active HIV-1 infection (Asin et al, 2004). Although epithelial cells of the FRT may or may not support active HIV-1 infection, they have been shown to transmit infectious virus to target cells (Stoddard et al, 2007). …”
Section: Resultsmentioning
confidence: 99%
“…A few studies have proposed that HIV-1 gp120 interacts with transmembrane heparan sulfate proteoglycans (syndecans) on genital epithelial cells [18,20]. Another study found that glycoprotein 340-a splice variant of salivary agglutinin expressed on cervical and vaginal epithelia-specifi cally bound the HIV envelope and enhanced passage of HIV to susceptible leukocytes [24]. One group found that β1-integrin on explant cervical epithelium bound virions, presumably via fi bronectin, which is abundant in human semen and may coat the envelope of seminal virions, although this fi nding was not observed in all explants [12].…”
Section: Anatomic Sites For Hiv Invasion In the Female Genital Tractmentioning
confidence: 97%
“…Therefore, HS contributes preferentially to the transcytosis of X4-specific HIV-1 (Vives et al 2005). gp340 is a scavenger receptor on macrophages and endometrial and endocervical epithelial cells (Cannon et al 2008;Stoddard et al 2007). Splice variant of gp340, called salivary agglutinin (SAG), binds HIV-1 and inhibits infection (Wu et al 2003(Wu et al , 2004.…”
Section: Syndecansmentioning
confidence: 99%
“…Splice variant of gp340, called salivary agglutinin (SAG), binds HIV-1 and inhibits infection (Wu et al 2003(Wu et al , 2004. gp340/SAG binds HIV-1 gp120 near to the base of V3 loop at the site which contributes to CDi epitope formation, including the peptide CTRPNYNKRKRIHIG (Stoddard et al 2007;Wu et al 2004). This interaction seems to be protein-protein based, without direct contribution of gp120 glycans.…”
Section: Syndecansmentioning
confidence: 99%
See 1 more Smart Citation